Circular Project Selection: How Companies Can Evaluate Circular Innovation Projects - Anja Eisenreich (MDPI AG, 2021)
For a transition toward the circular economy (CE) at the firm level, circular innovations are an essential requirement. Many companies are still hesitant to introduce circular solutions, as their future success chances are difficult to predict. Circular solutions often imply a high uncertainty and complexity because they are designed over multiple life cycles and are strongly interconnected with diverse stakeholders. Therefore, an effective selection process tailored to circular innovation is of great advantage. This study examines circular project selection by investigating selection processes and evaluation criteria for circular innovation management. A qualitative research design was chosen, including 18 in-depth interviews with CE experts and representatives from CE pioneer companies. Findings on the selection process show that circular innovation projects are often embedded in a strategic CE framework decision. Whereas idea generation is usually approached bottom-up involving different stakeholders, project evaluation is rather performed top-down by top management or in cross-functional teams. Furthermore, the study discusses evaluation criteria and their CE implications in detail and structures them into a criteria framework that can be used in multi-criteria decision models. This paper makes a theoretical contribution by connecting innovation and CE literature and by providing new knowledge on the still scarcely explored topic of circular project selection. As practical contribution, the study guides managers on how to approach project selection in circular innovation management and thus supports their development toward a CE.